IR region challenges: Photon or thermal detectors? Outlook and means - Sizov, F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Infrared (IR) detectors play now an increasing role in different areas of human activity (e.g., security and military applications, tracking and targeting, environmental surveillance, fire and harvest control, communications, law enforcement, space surveillance of the Earth, medical diagnostics, etc.). Discussed in the paper are issues associated with the development and exploitation of up to date basic IR radiation detectors and arrays. Recent progress of basic for applications focal plane arrays (FPAs) that has rendered significant influence on infrared imaging is analyzed, and comparison of FPA detector performance characteristics is described with account of operational conditions and performance limits.